FORMULATION AND INVESTIGATION OF POLYMERIC MULTIPLE UNIT PELLET SYSTEMS CONSISTING OF SUSTAINED RELEASE GLIMEPIRIDE AND IMMEDIATE RELEASE ATORVASTATIN CALCIUM - BHARAT BIJAPUR; GOWDA DV; VISHAL GUPTA N; SHAILESH THIRUMALESHWAR; PRAVEEN SIVADASU; MANJUNATH M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present work was to develop novel fixed-dose combinations (FDCs) for improvement of glucose tolerance in type II diabetes mellitus patients associated with dyslipidemia. Methods: Multiple unit pellet systems (MUPSs) consisting of sustained release (SR) glimepiride and immediate release atorvastatin calcium pellets were formulated. The SR glimepiride pellets were prepared using a combination of locust bean gum and gum ghatti/guar gum. Similarly, the immediate release of atorvastatin calcium pellets was prepared using locust bean gum suspension as a binder. Results: The formulated pellets were characterized using Fourier transform infrared spectroscopy (FTIR) and Differential scanning calorimetry (DSC). Further, surface morphology of the formulated pellets was done by scanning electron microscopy (SEM). FT-IR and DSC studies suggested that there were no chemical interactions between the drug and natural polymers. SEM studies revealed that formulated pellets were in spherical shape. Based on in vitro evaluation, the SR glimepiride formulation developed using a combination of 2% locust bean gum and 2.5% gum ghatti polymers sustained the release of the drug up to 12 h. Similarly, the immediate release atorvastatin calcium formulation containing 1% w/w locust bean gum suspension as a binder and 7% croscarmellose sodium showed fast disintegration of pellets. The in vivo studies in albino Wistar rat revealed that there was an improvement in bioavailability of the drugs. Stability studies showed that there were no significant changes in the drug content and physical appearance of the prepared SR glimepiride and immediate release atorvastatin pellet formulations. Conclusion: Thus, the formulated FDC as MUPS can be used as an alternative approach for treating diabetes mellitus-induced dyslipidemia.